Analysis of Fabrication Work Progress Based on Time Duration and Component Weight at PT. DIP Engineering - Oktavia, Rantini Dwi; Hayati, Nahrul (JURNAL SINTAK, 2025)
This study aims to analyze the progress of fabrication work at PT. DIP Engineering based on time parameters and component weight. The research method used is descriptive quantitative by analyzing secondary data of daily production output and inter-stage durations. The results show that peak activity occurred at the end of May, followed by a decline in early June due to design revisions and stage transitions. Duration analysis identified the waiting time from fit-up to welding as the main bottleneck, with an average of 5.42 days (73% of the total 7.42-day cycle). Pearson correlation test showed a strong and significant positive relationship between weight and quantity of item in the welding and visual inspection stages, although the coefficient of determination indicates that other factors such as item complexity also have a major influence. The study concludes that monitoring based on weight and time data provides objective insights for production planning, and optimization efforts should be focused on reducing queues at the welding stage to accelerate the overall production cycle.